Global Health in the Anthropocene: Moving Beyond Resilience and Capitalism; Comment on "Health Promotion in an Age of Normative Equity and Rampant Inequality" - Remco van de Pas (Kerman University of Medical Sciences, 2017)
There has been much reflection on the need for a new understanding of global health and the urgency of a paradigm shift to address global health issues. A crucial question is whether this is still possible in current modes of global governance based on capitalist values. Four reflections are provided. (1) Ecological-centered values must become central in any future global health framework. (2) The objectives of 'sustainability' and 'economic growth' present a profound contradiction. (3) The resilience discourse maintains a gridlock in the functioning of the global health system. (4) The legitimacy of multi-stakeholder governance arrangements in global health requires urgent attention. A dual track approach is suggested. It must be aimed to transform capitalism into something better for global health while in parallel there is an urgent need to imagine a future and pathways to a different world order rooted in the principles of social justice, protecting the commons and a central role for the preservation of ecology.